Characteristics of Lahat Robusta Coffee Cupping Scores Based on Natural Post-Harvest Processing - Ricky Rikardo; Dias Indrasti; Dian Herawati (PERTETA, 2026)
Robusta coffee from Lahat Regency, South Sumatra, is one of the leading commodities with quality potential that needs to be supported by proper post-harvest processing to achieve specialty (fine Robusta) quality standards. Natural post-harvest processing is known to form unique sensory characteristics through natural fermentation during drying. This study aimed to evaluate the cupping score characteristics of Lahat Robusta coffee based on natural post-harvest processing. Coffee bean samples were processed using the natural method to a moisture content of 10–11%, roasted, and evaluated using a cupping test by certified R-graders in accordance with Fine Robusta Standards and Protocols for the attributes of aroma/fragrance, flavor, aftertaste, salt or acid, bitter or sweet, mouthfeel, uniform cup, balance, clean cup, overall, taints-faults, and total scores. The results showed that Lahat Robusta coffee with natural post-harvest processing produced superior characteristics, with a final cupping score of 83.88, placing it in the specialty coffee category. The resulting sensory profile was dominated by the attributes of brown sugar, honey, dark chocolate, hazelnut, fresh fruity, acidic, nutty, cereally, and spicy. Natural post-harvest processing has proven to be effective in enriching flavor precursor compounds. Lahat Robusta coffee has the potential for regional authenticity and high quality. These findings can support the development of quality and strengthen the identity of Lahat Robusta coffee at the national scale.